New Crystal Form of Midazolam Hydrochloride and Its Preparation Method

By using mixed solvents and controlling temperature under different crystallization conditions, new crystal form III and crystal form VI of midazolam hydrochloride were prepared, which solved the problems of existing crystal form unstable and degraded impurities, achieved high purity and stability, and was suitable for industrial production.

CN116041351BActive Publication Date: 2025-06-03成都硕德药业有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210555747.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-05-20
Filing Date
2022-05-20
Publication Date
2025-06-03
Estimated Expiration
2042-05-20

AI Technical Summary

Technical Problem

The crystal form of existing midazolam hydrochloride is unstable, prone to degradation of impurities, and is not suitable for large-scale production.

Method used

New crystal forms III and crystal forms VI of midazolam hydrochloride were developed, and crystal forms with good physical and chemical stability were prepared by using mixed solvents and controlling temperature under different crystallization conditions.

Benefits of technology

It achieves high purity and stability of the crystal form, is suitable for industrial production, reduces the risk of degrading impurities, and improves the reproducibility of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This application relates to the field of drug crystal forms, and specifically relates to midazolam hydrochloride crystal forms III and VI and their preparation methods. The crystal form III of the compound of formula (I) obtained in the present invention has good physical stability and chemical stability, and the crystallization solvent used has low toxicity and low residue, which is more suitable for large-scale production and scale-up.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of drug crystal forms, and particularly relates to midazolam hydrochloride crystal forms III and VI and a preparation method thereof. Background Art

[0002] Midazolam oral solution was developed by Roche Pharmaceuticals and was launched in the United States on October 15, 1998. It is used for sedation, anti - anxiety, and anterograde amnesia in pediatric patients (6 months - 16 years old) before diagnosis, treatment, endoscopic procedures, or anesthesia induction. The active ingredient of midazolam oral solution is midazolam hydrochloride, and the chemical name of this compound is 8 - chloro - 6-(2 - fluorophenyl)-1 - methyl - 4H - imidazo[1,5 - ][1,4]benzodiazepine hydrochloride, and its structural formula is shown as formula (I):

[0003]

[0004] Patent CN201811539800.5 discloses crystal forms A and B of midazolam hydrochloride. According to the report of this patent, when preparing crystal form A, it needs to be heated to 85°C, and the drying process also needs to be carried out under vacuum conditions at 80 - 100°C. The risk of generating degradation impurities will increase during the above - mentioned process; the preparation method of crystal form B is static crystallization, and the target crystal form can only be obtained after standing for 5 days. This method is not suitable for large - scale industrial production. Patent CN201110119221.7 discloses a preparation method of midazolam hydrochloride crystallization. This method is to react midazolam with midazolam dihydrochloride, and the obtained solid is named crystal form C. According to the report of patent CN201811539800.5, crystal form C will undergo crystal transformation under high - temperature, high - humidity, and light conditions, and its chemical properties are also unstable.

[0005] Therefore, it is necessary to develop a new crystal form of midazolam hydrochloride with a simple preparation method, high stability, high purity, and suitable for industrial production. Summary of the Invention

[0006] The present invention aims to provide midazolam hydrochloride crystal forms III and VI, and solves the problems of unstable existing crystal forms, high degradation impurities, and unsuitability for large - scale production.

[0007] The present invention provides a crystal form III of a compound represented by formula (I), and its X-ray powder diffraction pattern has characteristic peaks at 2θ angles of 7.48° ± 0.2°, 9.92° ± 0.2°, 11.32° ± 0.2°, 12.82° ± 0.2°, 13.94° ± 0.2°, 16.02° ± 0.2°, 17.38° ± 0.2°, 19.19° ± 0.2°, 20.66° ± 0.2°, 23.02° ± 0.2°, 24.20° ± 0.2°, 24.72° ± 0.2°, 25.74° ± 0.2°, 28.56° ± 0.2° and 29.94° ± 0.2°.

[0008] The compound represented by formula (I) can obtain different crystallization products under different crystallization conditions. The obtained crystallization products were detected by XRD and TGA, and it was found that the compound represented by formula (I) can obtain a crystal form with good stability under conventional crystallization conditions, which we call crystal form III.

[0009] The crystal form III in this application uses Cu-Kα radiation, and the X-ray powder diffraction pattern expressed in 2θ angle, which has characteristic peaks near about 7.48° ± 0.2°, 9.92° ± 0.2°, 11.32° ± 0.2°, 12.82° ± 0.2°, 13.94° ± 0.2°, 16.02° ± 0.2°, 17.38° ± 0.2°, 19.19° ± 0.2°, 20.66° ± 0.2°, 23.02° ± 0.2°, 24.20° ± 0.2°, 24.72° ± 0.2°, 25.74° ± 0.2°, 28.56° ± 0.2° and 29.94° ± 0.2°.

[0010] Preferably, the X-ray powder diffraction pattern of the crystal form III is substantially as Figure 4 shown.

[0011] The thermogravimetric analysis pattern (TGA) of the crystal form III is as Figure 5 shown, and the weight loss in the range of 30 - 120 °C is about 4.73% - 5.95%.

[0012] The single crystal structure of the crystal form III is as Figure 6 shown, and this structure shows that the crystal form III contains 1 molecule of crystallization water.

[0013] The water content of the crystal form III is about 4.73% - 5.95%.

[0014] The present invention also relates to a method for preparing crystal form III, and the method includes the following three:

[0015] (1) Midazolam was added to isopropanol, stirred and dissolved at room temperature, then water was added. The solution was transferred to an ice bath and stirred, and an HCl / ethanol solution was added dropwise until a large amount of solid precipitated. Then n-heptane was added dropwise and stirred overnight at room temperature, and filtered to obtain Crystal Form III.

[0016] (2) The compound shown in formula (I) was added to a mixed solvent, stirred at 15 - 30 °C for 5 - 24 hours, and filtered to obtain Crystal Form III.

[0017] (3) The compound shown in formula (I) was added to a mixed solvent, heated to 50 - 65 °C to completely dissolve the solid, cooled to 40 - 50 °C, and seeds of 0.5% - 2% Crystal Form III were added. Then it was slowly cooled to 15 - 30 °C for crystallization to obtain Crystal Form III.

[0018] In the above-mentioned methods, the solvent in method (2) or (3) is a mixed solvent. One of the mixed solvents is water; the other solvent is selected from one or more of methanol, n-propanol, isopropanol, acetone, butanone, acetonitrile, tetrahydrofuran, 1,4-dioxane, N,N-dimethylformamide, preferably isopropanol and acetonitrile. The water content in the mixed solvent is 1% - 10%, preferably 1% - 3%.

[0019] The present invention provides a Crystal Form VI of the compound shown in formula (I), and its X-ray powder diffraction pattern has characteristic peaks at 2θ angles of 11.66°, 12.86°, 14.52°, 15.90°, 16.96°, 18.42°, 20.60°, 23.08°, 24.38°, 25.64° and 27.04°.

[0020] The Crystal Form VI in this application uses Cu-Kα radiation, and the X-ray powder diffraction pattern is expressed in 2θ angles, and has characteristic peaks near about 11.66°, 12.86°, 14.52°, 16.96°, 18.42°, 20.60°, 23.08°, 24.38°, 25.64° and 27.04°.

[0021] Preferably, the X-ray powder diffraction pattern of the Crystal Form VI is substantially as Figure 7 shown.

[0022] The thermogravimetric analysis pattern (TGA) of the Crystal Form VI is as Figure 8 shown, and the weight loss within the range of 30 - 120 °C is less than 0.5%.

[0023] The single crystal structure of the Crystal Form VI is as Figure 9 shown, and this structure shows that the Crystal Form VI is an anhydrous substance.

[0024] The present invention also relates to a method for preparing polymorph VI, which is characterized in that the method is as follows: Midazolam is added to isopropanol and stirred to dissolve at 15-30 °C, then the solution is transferred to an ice bath and HCl / ethanol solution is slowly added dropwise to obtain polymorph VI.

[0025] In the above method, the dosage of the HCl / ethanol solution is 1.1-1.5 times the equivalent of midazolam.

[0026] The beneficial effects brought by the present invention are as follows:

[0027] 1. Through accelerated stability studies, it is found that the polymorph III prepared in this application has good physical and chemical stability.

[0028] 2. The preparation method of polymorph III in this application has mild conditions and simple operation. While for polymorph A reported in the patent, it needs to be heated to 85 °C during preparation, and the drying process also needs to be carried out under vacuum conditions at 80-100 °C, which increases the risk of generating degradation impurities; the preparation method of polymorph B is static crystallization, and the target polymorph can only be obtained after standing for 5 days, and this method is not suitable for large-scale industrial production.

[0029] 3. By controlling the key parameters in the preparation process of polymorph III, the preparation method of this application can obtain a single polymorph, with good process reproducibility and high purity (HPLC purity > 99.8%), making the industrial production conditions controllable and conducive to large-scale industrialization. Description of the Drawings

[0030] Figure 1 XRD pattern of midazolam hydrochloride polymorph A

[0031] Figure 2 XRD pattern of midazolam hydrochloride polymorph B

[0032] Figure 3 XRD pattern of midazolam hydrochloride polymorph C

[0033] Figure 4 XRD pattern of midazolam hydrochloride polymorph III.

[0034] Figure 5 TGA pattern of midazolam hydrochloride polymorph III.

[0035] Figure 6 Single crystal structure of midazolam hydrochloride polymorph III.

[0036] Figure 7 XRD pattern of midazolam hydrochloride polymorph VI.

[0037] Figure 8 TGA pattern of midazolam hydrochloride polymorph VI.

[0038] Figure 9 It is the single crystal structure of midazolam hydrochloride form VI.

[0039] Figure 10 This is the XRD comparison spectrum of midazolam hydrochloride form C under accelerated conditions.

[0040] Figure 11 This is the XRD comparison spectrum of midazolam hydrochloride form III under accelerated conditions. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with the embodiments, but the present invention is not limited thereto. Any equivalent substitutions in the art made according to the disclosure of the present invention shall fall within the protection scope of the present invention.

[0042] The abbreviations used in this application are explained as follows:

[0043] XRD: X-ray powder diffraction

[0044] The X-ray powder diffraction (XRD) test described in Examples 1-13 and Comparative Example 3 of the present application was collected using a Liaoning Dandong Haoyuan DX-2700B powder diffractometer, and the specific parameters are as follows:

[0045]

[0046] The X-ray powder diffraction (XRD) test described in Comparative Examples 1 and 2 of the present application was collected using a Malvern Panalytical Empyrea powder diffractometer, and the specific parameters are as follows:

[0047]

[0048] TGA: Thermogravimetric Analyzer

[0049] The thermogravimetric analysis (TGA) described in the present application was performed using a METTLER TOLEDO model TGA-2, with a heating rate of 10°C / min, a temperature range of 30-300°C, and a nitrogen purge rate of 20 mL / min during the test.

[0050] KF: Karl Fischer Moisture Analyzer

[0051] The moisture content described in the present application is measured using a Karl Fischer titrator of model 870KF Titrino plus manufactured by Metrohm (Switzerland).

[0052] HPLC: High Performance Liquid Chromatography

[0053] The determination of the HPLC chromatogram was carried out using an Agilent 1260 DAD liquid chromatograph. In this application, the HPLC purity of polymorph III was determined by the following method:

[0054] (1) Chromatographic column: Inertsil ODS-3

[0055] (2) Detector: UV detector (wavelength 254 nm)

[0056] (3) Flow rate: 1.0 mL / min

[0057] (5) Test solution: Take 1 mg of this product, weigh accurately, dissolve and dilute with solvent to make a solution containing about 1 mg per 1 mL as the test solution

[0058] (6) Injection volume: 50 μl. The test solution was determined by automatic integration method, and the purity of midazolam hydrochloride in the test sample was calculated according to the peak area.

[0059] Room temperature: 15 - 30 °C

[0060] Solvent screening experiment

[0061] In order to discover new polymorphs of midazolam hydrochloride, the inventors added a certain amount of midazolam hydrochloride to different solvents and screened for new polymorphs by methods such as crystallization by cooling or suspension transformation.

[0062] Surprisingly, it was found that when the reaction solvent was a mixed solvent and the solvent contained a certain proportion of water, a new polymorph III could be obtained. When the reaction solvent was a single isopropanol, acetone or acetonitrile, a new polymorph VI could be obtained. The results are shown in Table 1 below.

[0063] Table 1 Experimental results of preparing new polymorphs with different solvent systems

[0064] Solvent system Crystal form Ethanol Crystal form C Ethanol: water = 7.5 mL: 0.05 mL Crystal form C Ethanol: water = 7.5 mL: 0.37 mL Crystal form C Isopropanol Crystal form VI Acetone Crystal form VI Acetonitrile Crystal form VI Isopropanol: water = 7.5 mL: 0.2 mL Crystal form III Acetonitrile: water = 7.5 mL: 0.1 mL Crystal form III Acetone: water = 1 mL: 0.1 mL Crystal form III Butanone: water = 1 mL: 0.1 mL Crystal form III Tetrahydrofuran: water = 1 mL: 0.1 mL Crystal form III 1,4 - Dioxane: water = 1 mL: 0.1 mL Crystal form III N,N - Dimethylformamide: water = 1 mL: 0.1 mL Crystal form III

[0065] As can be seen from Table 1 above, when using pure ethanol or ethanol-water mixed solvents with different proportions, the obtained product is polymorph C; when using other water-containing solvents as the reaction solvent, such as isopropanol-water mixed solvent, acetone-water mixed solvent, butanone-water mixed solvent, acetonitrile-water mixed solvent, tetrahydrofuran-water, 1,4-dioxane-water, N,N-dimethylformamide-water, the obtained product is polymorph III.

[0066] Example 1: Preparation of midazolam hydrochloride polymorph III

[0067] 1.02 g of midazolam was added to a flask and dissolved in 6 mL of isopropanol by stirring at room temperature. Then 200 μL of water was added, and the solution was transferred to an ice bath and stirred. 0.26 g of HCl / ethanol solution (HCl content: 15%) was slowly added dropwise. After the addition, no solid precipitated. Then another 0.72 g of HCl / ethanol solution was added dropwise, and a large amount of solid precipitated after the addition. Then 10 mL of n - heptane was added dropwise using a dropping funnel and stirred overnight at room temperature. The mixture was filtered to obtain a white powdery solid.

[0068] Thermogravimetric analysis (TGA) was performed on the obtained sample. The weight loss in the range of 30 - 120 °C was 5.50%. The water content of the crystalline sample was determined by the KF method to be 5.79%. This crystal form was significantly different from the three reported crystal forms and was named crystal form III.

[0069] X - ray powder diffraction was performed using Cu - ka radiation. Its diffraction pattern has the diffraction angle, interplanar spacing, and relative intensity shown in the following table:

[0070] Table 2 Diffraction angle, interplanar spacing, and relative intensity of crystal form III

[0071]

[0072] The error of the diffraction angle of 2θ is ±0.20°.

[0073] Furthermore, the crystalline form III of midazolam hydrochloride prepared in Example 1 has an X - ray powder diffraction pattern substantially as follows: Figure 4 as shown.

[0074] Example 2: Preparation of crystalline form III of midazolam hydrochloride

[0075] 100 mg of midazolam hydrochloride was added to a mixed solvent of 1 mL of isopropanol and 100 μL of water and suspended at room temperature for 12 h to obtain a white powdery solid. Its thermogravimetric analysis pattern and powder diffraction data were basically consistent with those of Example 1.

[0076] Example 3: Preparation of crystalline form III of midazolam hydrochloride

[0077] 100 mg of midazolam hydrochloride was added to a mixed solvent of 1 mL of acetone and 100 μL of water and suspended at room temperature for 12 h to obtain a white powdery solid. Its thermogravimetric analysis pattern and powder diffraction data were basically consistent with those of Example 1.

[0078] Example 4: Preparation of crystalline form III of midazolam hydrochloride

[0079] 100 mg of midazolam hydrochloride was added to a mixed solvent of 1 mL of methyl ethyl ketone and 100 μL of water, and the mixture was suspended at room temperature for 12 h to obtain a white powdery solid. Its thermogravimetric analysis pattern and powder diffraction data were basically consistent with those of Example 1.

[0080] Example 5: Preparation of Crystal Form III of Midazolam Hydrochloride

[0081] 100 mg of midazolam hydrochloride was added to a mixed solvent of 1 mL of acetonitrile and 100 μL of water, and the mixture was suspended at room temperature for 12 h to obtain a white powdery solid. Its thermogravimetric analysis pattern and powder diffraction data were basically consistent with those of Example 1.

[0082] Example 6: Preparation of Crystal Form III of Midazolam Hydrochloride

[0083] 100 mg of midazolam hydrochloride was added to a mixed solvent of 1 mL of tetrahydrofuran and 100 μL of water, and the mixture was suspended at room temperature for 12 h to obtain a white powdery solid. Its thermogravimetric analysis pattern and powder diffraction data were basically consistent with those of Example 1.

[0084] Example 7: Preparation of Crystal Form III of Midazolam Hydrochloride

[0085] 100 mg of midazolam hydrochloride was added to a mixed solvent of 1 mL of 1,4-dioxane and 100 μL of water, and the mixture was suspended at room temperature for 12 h to obtain a white powdery solid. Its thermogravimetric analysis pattern and powder diffraction data were basically consistent with those of Example 1.

[0086] Example 8: Preparation of Crystal Form III of Midazolam Hydrochloride

[0087] 100 mg of midazolam hydrochloride was added to a mixed solvent of 1 mL of N,N-dimethylformamide and 100 μL of water, and the mixture was suspended at room temperature for 12 h to obtain a white powdery solid. Its thermogravimetric analysis pattern and powder diffraction data were basically consistent with those of Example 1.

[0088] Example 9: Preparation of Crystal Form III of Midazolam Hydrochloride

[0089] 1.00 g of midazolam hydrochloride was added to a mixed solvent of 8 mL of isopropanol, 8 mL of dichloromethane and 500 μL of water. After stirring and dissolving, the mixture was allowed to stand and volatilize at room temperature to obtain a granular single crystal product. Its thermogravimetric analysis pattern and powder diffraction data were basically consistent with those of Example 1. Single crystal analysis was performed on this sample, and its unit cell parameters are shown in Table 3, and the single crystal structure is as Figure 6 shown.

[0090] Table 3 Unit Cell Parameters of Crystal Form III

[0091]

[0092]

[0093] Example 10: Preparation of Midazolam Hydrochloride Polymorph III

[0094] Dissolve 0.50 g of midazolam hydrochloride in a mixed solvent of 15 mL of acetonitrile and 200 μL of water. Heat the solution to 65 °C until the solid is completely dissolved, then cool it to 40 °C. Add 1% of the seed crystals prepared in Example 1 and continue stirring for 1 h. Slowly cool the solution to room temperature and stir to crystallize. Filter to obtain a white powdery solid. The thermogravimetric analysis pattern and powder diffraction data are basically the same as those in Example 1.

[0095] Example 11: Preparation of Midazolam Hydrochloride Polymorph III

[0096] Dissolve 0.50 g of midazolam hydrochloride in a mixed solvent of 7.5 mL of isopropanol and 200 μL of water. Heat the solution to 65 °C until the solid is completely dissolved, then cool it to 50 °C. Add 1% of the seed crystals prepared in Example 1. Slowly cool the solution to room temperature and stir to crystallize. Filter to obtain a white powdery solid. The thermogravimetric analysis pattern and powder diffraction data are basically the same as those in Example 1.

[0097] Example 12: Preparation of Midazolam Hydrochloride Polymorph VI

[0098] Add 1.00 g of midazolam to 10 mL of isopropanol and stir to dissolve at room temperature. Transfer the solution to an ice bath and slowly add 0.90 g of HCl / ethanol solution (HCl content is 15%). After the addition, stir overnight at room temperature to obtain 0.86 g of a white powdery solid.

[0099] Perform thermogravimetric analysis (TGA) on the obtained sample. The weight loss in the range of 30 - 120 °C is 0.38%. This polymorph is significantly different from the three previously reported polymorphs and is named polymorph VI.

[0100] Perform X-ray powder diffraction using Cu-Kα radiation. The diffraction pattern has the diffraction angles, interplanar spacings, and relative intensities shown in the following table:

[0101] Table 4 Diffraction Angles, Interplanar Spacings, and Relative Intensities of Polymorph VI

[0102]

[0103] The error of the diffraction angle 2θ is ±0.20°.

[0104] Furthermore, the midazolam hydrochloride polymorph VI prepared in Example 12 has an X-ray powder diffraction pattern substantially as follows: Figure 7 as shown.

[0105] Example 13: Preparation of Midazolam Hydrochloride Polymorph VI

[0106] 1.03 g of midazolam hydrochloride was added to 5 mL of isopropanol and suspended at room temperature for 18 h to obtain a white powdery solid. Its thermogravimetric analysis pattern and powder diffraction data were basically consistent with those of Example 12.

[0107] Example 14: Preparation of Crystal Form VI of Midazolam Hydrochloride

[0108] 200 mg of midazolam hydrochloride was added to a mixed solvent of 1 mL of methanol and 1 mL of dichloromethane. After stirring and dissolving, it was left to stand and volatilize at room temperature to obtain a granular single crystal product. Its thermogravimetric analysis pattern and powder diffraction data were basically consistent with those of Example 12. Single crystal analysis was performed on this sample, and its unit cell parameters are shown in Table 5, and the single crystal structure is as Figure 9 shown.

[0109] Table 5 Unit Cell Parameters of Crystal Form VI

[0110]

[0111]

[0112] Comparative Example 1: Preparation of Comparative Crystal Form A

[0113] 3.00 g of midazolam was added to a flask and 45 mL of ethanol. After stirring and dissolving at room temperature, the solution was transferred to an ice bath and stirred, and 2.95 g of HCl / ethanol solution (HCl content was 15%) was slowly added dropwise. A solid precipitated immediately after the addition was completed. The above solution was transferred to an 80 °C oil bath and stirred until the solid was completely dissolved, then cooled to 60 °C, and 68 mL of n - heptane was added dropwise through a dropping funnel. A solid precipitated during the addition process, and then it was transferred to an ice bath and stirred for crystallization for 2 h. It was filtered, and the filter cake was washed with n - heptane. The obtained solid was dried in a vacuum drying oven at 80 °C for 14 h to obtain a white powdery solid, which was crystal form A. Its X - ray powder diffraction pattern is as Figure 1 shown.

[0114] Comparative Example 2: Preparation of Comparative Crystal Form B

[0115] 5.00 g of midazolam was added to a flask and 50 mL of isopropanol. After stirring and dissolving at room temperature, the solution was transferred to an ice bath and the seed crystal of crystal form B was added, and 4.56 g of HCl / ethanol solution (HCl content was 15%) was slowly added dropwise. After the addition was completed, stirring was continued for 3 hours, and then it was filtered. The obtained solid was dried at room temperature to obtain a white powdery solid, which was crystal form B. Its X - ray powder diffraction pattern is as Figure 2 shown.

[0116] Comparative Example 3: Preparation of Comparative Crystal Form C

[0117] 10.02 g of midazolam was added to a flask and dissolved in 140 mL of ethanol. After stirring and dissolving at room temperature, the solution was transferred to an ice bath and stirred, and 10.03 g of HCl / ethanol solution (HCl content: 15%) was slowly added dropwise. After the addition was complete, stirring was continued until a solid precipitated. Then, 140 mL of n-heptane was added dropwise using a dropping funnel, and stirring was continued at room temperature for 1 hour. The mixture was filtered to obtain a white powdery solid, which was Form C. Its X-ray powder diffraction pattern is as Figure 3 shown.

[0118] Test Example 1: Stability investigation experiment

[0119] To investigate the stability of the crystalline forms III, VI of midazolam hydrochloride prepared in the present invention and the crystalline forms A, B, C of the comparative examples, the crystalline form A prepared in Comparative Example 1, the crystalline form B prepared in Comparative Example 2, the crystalline form C prepared in Comparative Example 3, the crystalline form III prepared in Example 1, and the crystalline form VI prepared in Example 12 were placed under two accelerated test conditions of 25 °C, 60% RH and 40 °C, 75% RH for 3 months. Samples were taken at 1 month, 2 months, and 3 months, and XRD and HPLC were tested and compared with the results at 0 day. The results are as follows:

[0120] Table 6 Accelerated stability test data of different crystalline forms

[0121]

[0122] As can be seen from Table 6 and Figure 10 it can be known that the crystal forms of A, B, C cannot maintain stability under the accelerated test conditions, and have been completely converted to crystalline form III after 1 month of acceleration at 25 °C and 40 °C.

[0123] As can be seen from Table 6 and Figure 11 it can be known that when the crystalline form III is placed under the accelerated test conditions for 3 months, the crystal form can maintain stability and the purity has not changed significantly.

[0124] In summary, the physical and chemical stabilities of the crystalline form III are superior to those of the crystalline forms A, B, and C.

[0125] Test Example 2: Bioavailability investigation

[0126] Pharmacokinetics experiment in rats

[0127] 1. Test purpose

[0128] To investigate the concentration level of the active ingredient in plasma and its pharmacokinetic characteristics after single oral administration of different crystalline forms of midazolam hydrochloride to rats at the same dosing dose.

[0129] 2. Materials and methods

[0130] 2.1 Test drug

[0131] Midazolam Hydrochloride Polymorph A, a white powdery solid, prepared in Comparative Example 1;

[0132] Midazolam Hydrochloride Polymorph B, a white powdery solid, prepared in Comparative Example 2;

[0133] Midazolam Hydrochloride Polymorph C, a white powdery solid, prepared in Comparative Example 3;

[0134] Midazolam Hydrochloride Polymorph Ⅲ, a white powdery solid, prepared in Example 1;

[0135] Midazolam Hydrochloride Polymorph VI, a white powdery solid, prepared in Example 12;

[0136] 2.2 Test animals

[0137] Thirty SD rats, 15 males and 15 females, weighing 220 - 240 g, were purchased on behalf by Chengdu Ensville Biotechnology Co., Ltd. from Hunan Slack Jingda Experimental Animal Co., Ltd., with the license number: SCXK(Xiang)2019 - 0004.

[0138] 2.3 Test methods

[0139] After the test drug was formulated into a uniform suspension of 1.25 mg / kg with corn oil, it was immediately orally administered to the rats at a volume of 5 mL / kg. Blood samples of 0.1 mL were taken from the jugular vein before dosing and at 15 min, 30 min, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, and 24 h after dosing, placed in EDTA - K2 tubes, centrifuged at 3000 r / min for 10 min to separate plasma, and stored frozen at - 80 °C in a refrigerator.

[0140] 2.4 LC / MS / MS bio - sample analysis:

[0141] 50 μL of plasma was mixed with 5 μL of working solution or blank diluent, 150 μL of acetonitrile precipitant containing internal standard was added, vortex - shaken for 2 min, centrifuged at 12000 r / min for 10 min, 2 μL of the supernatant was mixed with 200 μL of pure water:acetonitrile (1:1), and then analyzed by injecting 3 μL.

[0142] 2.5 Test results:

[0143] Animal experiments were carried out on different polymorphs of midazolam hydrochloride. After single - oral administration to male and female rats, the average concentration (ng·mL-1) of API in plasma at different times was measured, and the average drug concentration - time curves in plasma after single - oral administration to male and female rats were plotted. The results showed that the bioavailability of Polymorph Ⅲ and Polymorph VI was significantly higher.

[0144] It will be apparent to those of ordinary skill in the art that various modifications and variations can be made to the compounds of the present application and their preparation methods without departing from the spirit or scope of the present application. Therefore, the scope of protection of the present application covers various modifications and variations made to the present application, as long as such modifications or variations are within the scope covered by the claims and their equivalent embodiments.

Claims

1. Polymorph III of the compound shown in formula (I), whose X-ray powder diffraction pattern has characteristic peaks at 2θ angles of 7.48° ± 0.2°, 9.92° ± 0.2°, 11.32° ± 0.2°, 12.82° ± 0.2°, 13.94° ± 0.2°, 16.02° ± 0.2°, 17.38° ± 0.2°, 19.19° ± 0.2°, 20.66° ± 0.2°, 23.02° ± 0.2°, 24.20° ± 0.2°, 24.72° ± 0.2°, 25.74° ± 0.2°, 28.56° ± 0.2° and 29.94° ± 0.2°.

2. The polymorph III of the compound shown in formula (I) according to claim 1, wherein, the X-ray powder diffraction pattern of the polymorph III of the compound shown in formula (I) is substantially as shown in Figure 4.

3. The polymorph III of the compound shown in formula (I) according to claim 1 or 2, wherein, the thermogravimetric analysis pattern of the polymorph III is as shown in Figure 5.

4. The polymorph III of the compound shown in formula (I) according to claim 1 or 2, wherein, the water content of the polymorph III is 4.73% - 5.95%.

5. A preparation method of the polymorph III of the compound shown in formula (I) as claimed in claim 1, wherein, add midazolam into isopropanol, stir and dissolve at room temperature, then add water, transfer the solution to an ice bath and stir, and dropwise add HCl / ethanol solution until a large amount of solid precipitates, then dropwise add n-heptane, and stir overnight at room temperature, filter to obtain polymorph III; or, the preparation method is: add midazolam hydrochloride into a mixed solvent, stir at room temperature, filter to obtain polymorph III; or, add midazolam hydrochloride into a mixed solvent, heat and stir until the solid completely dissolves, then add crystal seeds and cool to crystallize to obtain polymorph III; one of the mixed solvents is water, and the other solvent is selected from one or more of methanol, n-propanol, isopropanol, acetone, butanone, acetonitrile, tetrahydrofuran, 1,4-dioxane, N,N-dimethylformamide; the water content in the mixed solvent is 1% - 10%.

6. The preparation method of the polymorph III of the compound shown in formula (I) according to claim 5, wherein, one of the mixed solvents is water, and the other solvent is selected from isopropanol and acetonitrile; the water content in the mixed solvent is 1% - 3%.

Citation Information

Patent Citations

  • Process for the synthesis of 4h-imidazo [1,5-a] [1,4] benzodiazepines, in particular midazolam and salts thereof

    CN102241679A

  • Novel crystal form of midazolam hydrochloride and its preparation method

    CN111320632B

  • Preparation method and application of midazolam hydrochloride F crystal form

    CN113149992A